Coexistence of Structural and Dynamical Heterogeneity in Liquids Under Nanoconfinement - Xia, Yiqing; Cho, Hyeyoung; Risbud, Subhash H.; Bartl, Michael H.; Sen, Sabyasachi (Frontiers in Physics, 2020)
Spatiotemporal heterogeneity is one of the hallmarks of the relaxation dynamics associated with the glass transition. A key question in this regard is whether the dynamical heterogeneity has a structural origin. We report differential scanning calorimetry (DSC) data that reveal the presence of extreme spatial heterogeneity in the freezing dynamics of water (D2O) and the glass transition dynamics in the supercooled molecular liquid ortho-terphenyl (OTP), when these liquids are confined in nano-architected mesoporous silica with interconnected pores of different geometry. The results demonstrate, for the first time, that despite connectivity between the pores, nanoconfined water and OTP display distinct freezing/melting points and glass transition temperatures characteristic of each pore type. Viewed as a whole, these experimental results point to the coexistence of strong spatial heterogeneities over length scales of a few nanometers in the structure and dynamics of these liquids, suggesting a close mechanistic connection between them.